Synovial Chondromatosis of Hip in a Young Patient Salvaged With Mini Arthrotomy Without Hip Dislocation – A Case Report - Mahajan, Neetin P. (J Orthop Case Rep, 2021)
INTRODUCTION: Synovial chondromatosis is a rare, benign disorder of the synovium, which leads to loose body formation due to metaplastic transformation. It presents as multiple cartilaginous bodies in the synovial joints, bursae and in tendon sheaths. The diagnosis often delayed in hip involvement due to insidious onset of symptoms. Surgical management is essential to manage synovial chondromatosis, which includes hip dislocation and debridement, arthroscopic removal or using arthrotomy. CASE REPORT: A 20-year-old male patient presented with complaints of pain in the left hip since 1 year and difficulty in walking for 6 months. On examination, the patient had mild tenderness over the left hip with the restriction of joint movements. He had flexion deformity of 30°, adduction and external rotation deformity of 10 and 15°, respectively. X-ray of the pelvis with both hips anteroposterior and left hip lateral view revealed calcified nodular mass over superior, inferior part of the femoral head, and anterior part of the neck with decreased joint space. As the patient was disabled with pain, stiffness especially restricted flexion and abduction and difficulty in daily routine activities, we planned for surgical excision of the loose bodies. Using lateral approach to the hip, intra-articular loose bodies were removed through arthrotomy without hip dislocation. At present 2-year follow-up, the patient is having full hip range of motion with no difficulty in squatting, sitting cross-legged, and radiological examination showed no evidence of recurrence. The patient is fully satisfied with the chosen treatment and participating in running and other sports. CONCLUSION: Although hip synovial chondromatosis are rare, early surgical intervention with complete removal of loose bodies, joint distraction for 6 weeks to allow healing, and early initiation of hip physiotherapy helps in getting better outcome even in patients with early stages of hip arthritis. The early surgical intervention also prevents the progression of the joint degeneration, which in turn helps in postponing replacement surgeries in young patients. Satisfactory outcomes can be achieved by salvaging the natural hip joint.